Development of Augmented Reality (AR) Media to Improve Learning Outcomes on Earth Structure for Eighth Grade Students - Fazrin, Adisty Istiqomah; Agnafia, Desi Nuzul; Mashuri, Anwas (Integrated Science Education Journal, 2025)
Purpose of the study: This study aims to develop Augmented Reality (AR)-based learning media on the topic of Earth structure and its development to improve the learning outcomes of eighth-grade students. Methodology: The research employed a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate). The media was validated by media, content, and language experts. Practicality testing involved 25 students from MTsN 9 Ngawi and one science teacher. Effectiveness was tested through an independent sample t-test between the experimental and control groups. Main Findings: The AR media developed was deemed highly feasible with validation scores: 86% (media), 92% (content), and 95% (language). Practicality received scores of 96% from the teacher and 84% from students. The t-test showed a significant difference (p < 0.001) between the learning outcomes of the experimental and control groups. Novelty/Originality of this study: This study confirms that AR technology effectively improves students’ understanding of Earth structure concepts through interactive visualizations. It also boosts learning motivation and can be used independently both inside and outside the classroom. However, successful implementation requires adequate infrastructure and teacher training.